Odpowiedzi

2009-12-07T22:05:22+01:00
A)x²-5x-14=0
a=1
b=-5
c=-14
Δ=b²-4ac
Δ=(-5)²-4×1×(-14)=25+56=81
Δ>0
b)-x²-2x+15=0
a=-1
b=-2
c=15
Δ=b²-4ac
Δ=(-2)²-4×(-1)×15=4-=4+60=64
Δ>0
c)-4x²+2x-5=0
a=-4
b=2
c=-5
Δ=b²-4ac
Δ=(2)²-4×(-4)×(-5)=4-80=76
Δ<0
d)x²+10=7x
x²-7x+10=0
a=1
b=-7
c=10
Δ=b²-4ac
Δ=(-7)²-4×(1)×(10)=49-40=9
Δ>0
e)1+x+5x=0
6x+1=0
a=0
b=6
c=1
Δ=b²-4ac
Δ=(6)²-4×(0)×(1)=36
Δ>0
1 1 1
2009-12-07T22:08:05+01:00
A)x2-5x-14=0 a=1,b=-5,c=-14 delta=25+56=81
b)-x2-2x+15=0 a=-1,b=-2, c=15 delta = 64
c)-4x2+2x-5=0 a= -4,b=2,c=-5 delta = -76
d)x2+10=7x x²-7x+10=0 a=1, b= -7,c=10 delta = 9
e)1+x+5x=0 Czy to ostatnie to dobrze przepisane?
6x+1=0 a=0, b=6, c=1 delta = 36